2022
DOI: 10.3389/fendo.2022.907757
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Related to Oxidative Stress in Diabetic Cardiomyopathy

Abstract: Diabetes is a chronic metabolic disease that is increasing in prevalence and causes many complications. Diabetic cardiomyopathy (DCM) is a complication of diabetes that is associated with high mortality, but it is not well defined. Nevertheless, it is generally accepted that DCM refers to a clinical disease that occurs in patients with diabetes and involves ventricular dysfunction, in the absence of other cardiovascular diseases, such as coronary atherosclerotic heart disease, hypertension, or valvular heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 189 publications
0
30
0
Order By: Relevance
“… 13 , 32 Experiments with cardiomyocytes in culture have shown that supplementation with 14,15-EET reduces high glucose-induced hypertrophy 33 ; and reduction of EETs by CYP2J2 inhibition reduces the survival of adult ventricular myocytes submitted to reactive oxygen species (ROS), 34 a component of diabetes pathogenesis. 35 In experimental models of diabetes in rodents, mice with cardiac hypertrophy show a decrease in 14,15-EET 33 ; overexpression of CYP2J2 in mice attenuates diabetes-induced myocardial hypertrophy 36 ; and treatment of diabetic rats with a sEH inhibitor attenuates the reduction in cardiac outputs, left ventricular hypertrophy and fibrosis induced by hyperglycemia. 37 These experimental models provide strong evidence that EETs protect the diabetic heart, although how this might translate to a reduced risk of MI in humans is not known.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 32 Experiments with cardiomyocytes in culture have shown that supplementation with 14,15-EET reduces high glucose-induced hypertrophy 33 ; and reduction of EETs by CYP2J2 inhibition reduces the survival of adult ventricular myocytes submitted to reactive oxygen species (ROS), 34 a component of diabetes pathogenesis. 35 In experimental models of diabetes in rodents, mice with cardiac hypertrophy show a decrease in 14,15-EET 33 ; overexpression of CYP2J2 in mice attenuates diabetes-induced myocardial hypertrophy 36 ; and treatment of diabetic rats with a sEH inhibitor attenuates the reduction in cardiac outputs, left ventricular hypertrophy and fibrosis induced by hyperglycemia. 37 These experimental models provide strong evidence that EETs protect the diabetic heart, although how this might translate to a reduced risk of MI in humans is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of DM are characterized by decreased insulin signaling and changes in other signaling cascades, such as reduced AMPK and increased PKC and MAPK signaling, with resultant deleterious and maladaptive effects ( 3 ). DCMP’s clinical presentation may be preceded by myocardial structure changes and disturbed Ca 2+ signaling and metabolism ( 2 , 4 , 7 , 22 ). The myocardial structure changes, i.e., myocardial fibrosis, are favoured by increased collagen deposition and variations in extracellular matrix (ECM) protein structure ( 40 ).…”
Section: Diabetic Cardiomyopathy: Pathogenesis Disease Progression An...mentioning
confidence: 99%
“…Also, microvascular disease and cardiac capillary rarefaction contribute to severe cardiovascular morbidity and mortality in DM patients (3,4). Diabetes-related cardiomyopathy (DCMP) represents DM-induced morphofunctional cardiac abnormality after the presence of valvular, atherosclerotic, congenital, or hypertensive heart disease is excluded (5)(6)(7). Clinically, DCMP can be presented as two distinctive phenotypes, restrictive (heart failure with preserved ejection fraction, HFpEF) and dilated (heart failure with reduced ejection fraction, HFrEF) (8,9).…”
mentioning
confidence: 99%
“…These studies clearly show that NFAT is one of the most important molecules for inducing cardiac hypertrophy and GSK-3β is a critical negative regulator of cardiac hypertrophy signaling pathways. O -GlcNAcylation plays several roles in the impairment of cardiac function via modification of several of the proteins involved in progression to heart failure ( 3 , 28 , 29 ). In the present study, we used Ogt transgenic ( Ogt -Tg) mice and induced heart failure by transverse aortic constriction (TAC) surgery to investigate the role of O -GlcNAcylation in cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%